2019
DOI: 10.1186/s41476-019-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Zoom systems with tuneable lenses and linear lens movements

Abstract: Background: Classical zoom lenses are based on movements of sub-modules along the optical axis. Generally, a constant image plane position requires at least one nonlinear sub-module movement. This nonlinearity poses a challenge for the mechanical implementation. Tuneable lenses can change their focal length without moving along the optical axis. This offers the possibility of small system lengths. Since the focal range of tuneable lenses with significant aperture diameters is still limited, the use of tuneable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Looking back at Eq. (26) shows that the object to image distance for group 4 depending on F 0 1 can be written as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 3 2 ; 1 1 6 ; 3 5 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking back at Eq. (26) shows that the object to image distance for group 4 depending on F 0 1 can be written as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 3 2 ; 1 1 6 ; 3 5 4…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other methods for classical zoom lenses, [23][24][25] our method sets the main focus on mapping the first-order solution space applying traditional thin lens aberration equations. 26,27 This is based on an extension of ideas presented in our earlier work. 26 A similar approach for telescopes consisting of two adaptive mirrors was demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hybrid 3× optical zoom lens consisting of two solid sub-modules and a liquid lens was investigated by Lenk et al As shown in figure 9(a), the second sub-module was an adaptive liquid lens (APL™-1050, Holochip Corp). The adaptive liquid lens can not only be mechanically moved to realize the zooming function as a variator but it can also change its focal length simultaneously to realize the focusing function as a compensator to keep the image plane stationary [100]. Similarly, a 3× zoom system (the focal length range was 4.3 mm to 12.90 mm) consisting of a prism and two lens groups was proposed by Park et al As shown in figure 9(b), the second group was moved to the first group to obtain a long focal length to realize the zooming function.…”
Section: Optical Zoom Imaging Systems Using a Single Adaptive Liquid ...mentioning
confidence: 99%
“…With the rapid development of interferometry technology, phase-shifted interferometry (phaseshifting interferometry, PSI), the primary presentative of interferometry technology, becomes one of the main methods in modern measurement of optics surface shape. From the early phase-shift algorithm including the Hariharan algorithm and the Schwider algorithm to the current frequency-conversion phase-shift algorithm including the iterative algorithm and the principal element analysis method, we can come to a conclusion that the research of the frequency conversion phase shift algorithm has become the trend of modern phase-shift interferometry research [1]. Although the principal element analysis (PCA) and Advanced iterative algorithm (AIA) can be used to recover the phase information from a large number of phase-shifted interferogram efficiently [2][3][4][5], a series of error sources and the complexity of measured surface do exist in the actual measuring process [6,7].…”
Section: Introductionmentioning
confidence: 99%